Análisis socioeconómico de los comerciantes informales de la Bahía Huayna Cápac en la ciudad de Guayaquil – Ecuador - Llerena Moyano, Irving Javier (2023)
The Bay of the city of Guayaquil originated in the 1970s in which small merchant ships began to arrive at the Malecón docks, allowing it to be one of the places where several businesses were established by small retail merchants, who dedicated themselves to different types of sales, among the products that were sold the most were clothing and household appliances. Being a commercial sector with a lot of movement, a large number of informal vendors began to take over public spaces, and to move around the corners of said sector, this affected the volume of sales of formal merchants because their products were sold at higher prices. low. Informal trade occurs as a result of the lack of employment and is triggered below underemployment, the categorization of a group of people who are underemployed become economic units that are contemplated by law or are not or do not have the characteristics that are required to be part of a formal system, before the legislation, are called informal traders. Within the work that the Illustrious Municipality of Guayaquil has carried out is the implementation of the control executed by law enforcement officers specialized in informal commerce in sectors of Guayaquil, the Metropolitan Police is the entity in charge of caring for citizens within the city, it helps to maintain order between the formal and informal business community by lobbying various groups.